Traffic Psychology: Brazilian`s Research Revision - Maria Helena de Lemos Sampaio; Tatiana de Cássia Nakano (Psicologia, 2011)
The Traffic Psychology is an area that has been evident in recent years with changes in traffic rules and social demands. So can develop and achieve their goals it is necessary to understand trends and gaps concerning what has been researched in recent years. The present study compared published articles in the database Pepsic and Scielo with those presented at Brazilian Conference of Psychological Assessment. Publications were found between 2000 and 2009, with the results showing an increased interest in the area, primarily focused on research of personality and attention, using a variety of instruments, most are not specific to the context of traffic, apply in most driver’s candidates.